Pengaruh Teknik Desinfeksi dengan Berbagai Macam Larutan Desinfektan pada Hasil Cetakan Alginat terhadap Stabilitas Dimensional - Distrina Fitrian Sari; R. Rahadyan Parnaadji; Agus Sumono (Pustaka Kesehatan, 2013)
A Impression material that is often used is alginate. Alginate has Characters imbibition and syneresis properties that can cause dimensional changes alginate mold result. Another factor to consider is the control of transmission of infection from alginate, as alginate mold result became one of the agents of transmission of infection in the dentist, it is important to take action disinfection with a disinfectant solution. Type of laboratory experimental research with the study design The Post Test Control Group Design on 72 samples of alginate mold. Sample grouping consists of 9 groups , 1 control group and 8 treatment groups with soak and spray technique using a disinfectant solution for 10 minutes. In each treatment group dimensional stability changes, except the control group because the treatment is not used. Technique that gives greater influence on changes in dimensional stability is the soaking technique. But the use of a variety of different disinfectant solution did not impact on the mold result. There are significant differences in the dimensional stability of the disinfection technique. Techniques greater dimensional stability is changing soaking technique. But the use of various disinfectant materials do not have a significant effect on the dimensional stability of alginate mold result. Recommended spraying disinfection action and further research needs to done on alginate. Keywords: Alginate, Dimensional Stability, Infection Control